1991
DOI: 10.1080/00050069108258851
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural treatment programs and selectivity of speaking at follow-up in a sample of 25 selective mutes

Abstract: In a retrospective study, 25 children who had been selectively mute in school were followed up by means of questionnaires administered via their schools, 2–10 years after referral. Those given individual therapy programs with a behavioural content were more likely to have improved at follow‐up than those given standard, school‐based remedial programs. A further poor prognostic indicator was found to be an incidence of past or present mental illness in the immediate family. The present data provide preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…If we put these results together with family pathology investigated at the time of referral, it becomes evident that individual psychopathology and family psychopathology correspond with each other and may form the background for the high persistence and poor outcome of this disorder. Our results are in line with the 2-10 year follow-up study by Sluckin et al (1991) who also found a poor outcome associated with marked family psychopathology.…”
Section: Discussion S Limitation Of the Studysupporting
confidence: 82%
“…If we put these results together with family pathology investigated at the time of referral, it becomes evident that individual psychopathology and family psychopathology correspond with each other and may form the background for the high persistence and poor outcome of this disorder. Our results are in line with the 2-10 year follow-up study by Sluckin et al (1991) who also found a poor outcome associated with marked family psychopathology.…”
Section: Discussion S Limitation Of the Studysupporting
confidence: 82%
“…The majority of SM treatment studies are limited in the lack of comparison groups, but there has been one small group study comparing different SM treatments. Sluckin, Foreman, and Herbert (1991) conducted a follow‐up study of 25 children who were referred by their schools for treatment of SM. Eleven of these children participated in behavioral therapy that used a combination of shaping and stimulus fading procedures, while the remaining 14 children participated in school‐based remedial programs led by special needs teachers.…”
Section: The Present Reviewmentioning
confidence: 99%
“…The majority of the literature in this area consists of retrospective record reviews, uncontrolled case studies, and a small number of single‐participant experiments of varied methodological quality. To date there has been only one small non‐controlled treatment study (Krohn, Weckstein, & Wright, 1992) and one small group study comparing two different SM treatments (Sluckin, Foreman, & Herbert, 1991). The age range of the children studied is quite narrow, with only two studies describing interventions with older children (Bonovitz, 2003; Rye & Ullman, 1999).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The first study examined retrospectively the records for 25 children with SM treated either with behavioural therapy or a school-based remediation programme. The children treated with behavioural therapy showed a greater improvement compared to the group which received the school-based remediation intervention (Sluckin, Foreman, & Herbert, 1991). In the second and more recent study (Vecchio & Kearney, 2009) an alternating treatment design was applied in nine children with SM.…”
Section: Introductionmentioning
confidence: 99%